Augmented Reality KANGEN-AZI Eliminates Stunting through the Implementation of Sports Nutrition Classes Formulating PMT Based on Local Food Ingredients at SMANKOR - Budiman Agung Pratama; Nur Ahmad Muharram; Entin Srihadi Yanti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Augmented Reality KANGEN-AZI Stunting-Free through the Implementation of Sports Nutrition Class and Supplementary Feeding Formulation using Local Food Ingredients at SMANKOR Background: Adolescent athletes at SMANKOR (State Sports High School) face dual nutritional challenges: high nutrient demands for sports performance and the risk of stunting, which can hinder their physical and cognitive potential. Innovative and measurable nutritional interventions are needed to address this issue. To quantitatively measure the impact of a community service program integrating Augmented Reality (AR) KANGEN-AZI for sports nutrition education and the implementation of Supplementary Feeding (PMT) based on local food ingredients in stunting prevention efforts. This study employed a pre-test and post-test design involving 40 SMANKOR athletes. Quantitative data were collected through nutrition knowledge questionnaires, attitude scales, and nutritional status measurements (Body Mass Index for Age/BMI/A). The results showed a significant increase in the average nutrition knowledge score by 40.8% (from 62.5 to 88.0, p < 0.001). User engagement with AR KANGEN-AZI and acceptance of local food PMT were also high (average score > 4.2 on a 5-point scale). Physically, a positive shift in nutritional status was observed, with a reduction in the percentage of Underweight athletes from 15.0% to 5.0%. AR KANGEN-AZI proved to be an innovative and effective intervention model in enhancing nutritional literacy, changing behavior, and improving the nutritional status of adolescent athletes. The program quantitatively supports stunting prevention efforts and the optimization of sports achievement at SMANKOR